Establishing Reliability When Multiple Examiners Evaluate a Single Case-Part II: Applications to Symptoms of Post-Traumatic Stress Disorder (PTSD) - Cicchetti, Domenic; Fontana, Alan; Showalter, Donald (International Journal of Statistics in Medical Research, 2015)
In an earlier article, the authors assessed the clinical significance of each of 19 Clinician Administered PTSD Scale items and composite scores (CAPS-1) [1] when 12 clinicians evaluated a Vietnam era veteran. A second patient was also evaluated by the same 12 clinicians and used for cross-validation purposes [2]. The objectives of this follow-up research are: (1) to describe and apply novel bio-statistical methods for establishing the statistical significance of these reliability estimates when the same 12 examiners evaluated each of the two Vietnam era patients. This approach is also utilized within the broader contexts of the ideographic and nomothetic conceptualizations to science, and the interplay between statistical and clinical or practical significance; (2) to detail the steps for applying the new methodology; and (3) to investigate whether the quality of the symptoms (frequency, intensity); item content; or specific clinician affect the levels of rater reliability. The more typical (nomothetic) reliability research design focuses on group averages and broader principles related to biomedical issues, rather than the focus on the individual case (ideographic approach). Both research designs (ideographic and nomothetic) have been incorporated in this follow-up research endeavor.